2018
DOI: 10.1007/978-3-030-05819-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Control Methods for Mobile Virtual Exhibitions

Abstract: It is becoming popular to render art exhibitions in Virtual Reality (VR). Many of these are used to deliver at-home experiences on peoples' own mobile devices, however, control options on mobile VR systems are necessarily less flexible than those of situated VR fixtures. In this paper, we present a study that explores aspects of control in such VR exhibitions-specifically comparing 'on rails' movement with 'free' movement. We also expand the concept of museum audio guides to better suit the VR medium, explorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In fact, objective data from the logging of user's real-time positions, gaze directions, and controller interactions can complement questionnaires and reveal information that is otherwise impossible with subjective post-experiment questionnaires. For example, Li et al [38] recorded user gaze time on each painting in a virtual exhibition and compared it with the length of audio information, indicating how much they have engaged with each painting. Ch'ng and Cooke [12] analysed gaze patterns with multimodal behaviour for natural and task-based activities for users interacting with virtual objects and found that it can reveal interaction intention in terms of position and duration of visual attention.…”
Section: Experimental Methods For Engagement and Presencementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, objective data from the logging of user's real-time positions, gaze directions, and controller interactions can complement questionnaires and reveal information that is otherwise impossible with subjective post-experiment questionnaires. For example, Li et al [38] recorded user gaze time on each painting in a virtual exhibition and compared it with the length of audio information, indicating how much they have engaged with each painting. Ch'ng and Cooke [12] analysed gaze patterns with multimodal behaviour for natural and task-based activities for users interacting with virtual objects and found that it can reveal interaction intention in terms of position and duration of visual attention.…”
Section: Experimental Methods For Engagement and Presencementioning
confidence: 99%
“…Virtual objects can therefore provide a richer set of interaction possibilities beyond that of our natural physical constraints. Users have reported greater user experience and less simulator sickness when free controls for movements and manipulating information are provided in a virtual environment [38]. As user interactions around a virtual object are determined by the amount and variety of controls they have, object interactivity is arguably the most fundamental aspect of afordances virtual objects can have.…”
Section: Factors Afecting Engagement Around Virtual Objectsmentioning
confidence: 99%
“…An asymmetric co-occurrence matrix is created by calculating the concepts' relative co-occurrence frequencies. This matrix produces a two-dimensional concept map using a proprietary clustering algorithm based on Audio First [152][153][154][155][156] Audio and Multimodal Integration [157][158][159][160][161][162][163][164][165][166] Audio in Multimodal Comparison [167] Multimodal Experience [168][169][170][171][172][173][174][175] the spring-force model for the many-body problem [83]. The correctness of each concept in this semantic network generates a third hierarchical dimension, which displays the more general parent concepts at the higher levels.…”
Section: Computer-aided Qualitative Data Analysis Software (Caqdas)mentioning
confidence: 99%
“…Future use of HVAR should consider how perceived social presence in VR can be enhanced via the use of visual, aural and spatial cues. Previous research has shown that the use of virtual avatars in VR, even with a simple animated guide (Li, Tennent and Cobb, 2019), can increase the sense of social presence.…”
Section: The Spectator Experience With Armentioning
confidence: 99%